The Role of Phonesthemes in EFL Learners’ Word Acquisition - Zhao, Haotong (Theory and Practice of Second Language Acquisition, 2024)
Phonesthesia is one of the counterexamples of the arbitrariness of human languages. Although an individual word still appears arbitrary, a group of words bearing the same sound pattern might share similar meaning. This study investigated phonesthesia as a route to improving word acquisition. First, by comparing the guessing accuracy of phonesthemic versus prosaic words, we found phonesthemic words were significantly guessed better, suggesting EFL learners’ sensitivity to English phonesthemes prior to explicit instruction. Phonesthemes provide hints for learners trying to ascertain the meaning of an unknown word. However, according to the participants’ self-report, such sensitivity seems to lie somewhere in between pure clang association and genuine phonesthemic association. In another experiment, we examined the effect of phonesthemic knowledge, induced by explicit instruction, on the retention of phonesthemic words. The experimental group was taught 12 English phonesthemes while the control group wasn’t. It was revealed that learners equipped with phonesthemic knowledge could retain phonesthemic words significantly better over an interval. We argue this is due to an extension of the lexical network in learners’ minds. The second experiment further verified the facilitative role of phonesthemes in word retention. It is recommended that EFL teachers raise learners’ attention to phonesthesia, which may potentially assist in word learning.